2020
DOI: 10.33945/sami/jcr.2020.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Mediated Iron Nanoparticles and their Applications as Adsorbents for Water Treatment–A Review

Abstract: Plant-mediated synthesis of iron oxide nanoparticles has been increasingly drawing attention due to its ecofriendly nature and cost effectiveness. The biosynthesis technique engages plant secondary metabolites such as alkaloids, flavonoids, saponins, phenols, proteins, carbohydrates, glycosides, quinine, steroids, and tannins as reducers and/or stabilizers in the process of forming nanoparticles thereby replacing hazardous chemicals known with physical and chemical methods of nanomaterial synthesis. Biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…The catalyst function of LI-AgNPs was shown when it was discovered that the absorption region at 414 nm stayed practically intact and that less than 2.3% 4NP degradation continued after three days of to study the process of catalytic degradation. Findings revealed that dye elimination depended on the dose, and an increase in the percentage of catalyst was linked with a fast fall in the resultant mixture's absorbed effectiveness [29]. 50 minutes of contact at room temperature resulted in a 0.45 mg/mL catalytic load reduction of 72.36% of the MB.…”
Section: Catalytic Analysis Of Li-agnpsmentioning
confidence: 99%
“…The catalyst function of LI-AgNPs was shown when it was discovered that the absorption region at 414 nm stayed practically intact and that less than 2.3% 4NP degradation continued after three days of to study the process of catalytic degradation. Findings revealed that dye elimination depended on the dose, and an increase in the percentage of catalyst was linked with a fast fall in the resultant mixture's absorbed effectiveness [29]. 50 minutes of contact at room temperature resulted in a 0.45 mg/mL catalytic load reduction of 72.36% of the MB.…”
Section: Catalytic Analysis Of Li-agnpsmentioning
confidence: 99%
“…The development of nanocomposites containing biological materials has already been reported in a series of reviews in recent years [30,142,143]. There does, however, continue to be rapid development in the field.…”
Section: Magnetic Biological Nanocompositesmentioning
confidence: 99%
“…As a result, scientists have recognized and garnered significant attention for the potential of modifying adsorbents to enhance these factors. Commonly used adsorbents encompass a range of materials such as activated carbon, nanomaterials, agriculture, industrial wastes, clays, and biopolymers …”
Section: Adsorbentmentioning
confidence: 99%
“…Commonly used adsorbents encompass a range of materials such as activated carbon, nanomaterials, agriculture, industrial wastes, clays, and biopolymers. 23 Agricultural wastes are byproducts resulting from diverse agricultural and forestry practices. Using agricultural residue as adsorbents for treating wastewater has a number of benefits, including their widespread availability, affordability, quick recovery time, minimal processing needs, sustainability, chemical stability, and environmental friendliness.…”
Section: Adsorbentmentioning
confidence: 99%